The Managing Director's Global Policy Agenda, Spring Meetings 2021 : Bolstering the Recovery, Countering the Divergence. (Policy Papers; Policy Paper ;, 2021)
An unprecedented policy response and rapid progress in vaccine development have helped pull the global economy from a deep recession. But the outlook is marked by high uncertainty and great divergence. Carefully calibrated policies and stronger international cooperation are vital to safely exit the crisis. Transformative policies should aim for fast convergence toward a green, digital, and inclusive future.